(untitled) (Clinics, 2017)
OBJECTIVE: In this work, we attempted to develop a modified single-knot Kessler-loop lock suture technique and compare the biomechanical properties associated with this single-knot suture technique with those associated with the conventional modified Kessler and interlock suture techniques. METHODS: In this experiment, a total of 18 porcine flexor digitorum profundus tendons were harvested and randomly divided into three groups. The tendons were transected and then repaired using three different techniques, including modified Kessler suture with peritendinous suture, interlock suture with peritendinous suture, and modified Kessler-loop lock suture with peritendinous suture. Times required for suturing were recorded and compared among groups. The groups were also compared with respect to 2-mm gap load, ultimate failure load, and gap at failure. RESULTS: For tendon repair, compared with the conventional modified Kessler suture technique, the interlock and modified Kessler-loop lock suture techniques resulted in significantly improved biomechanical properties. However, there were no significant differences between the interlock and modified Kessler-loop lock techniques with respect to biomechanical properties, gap at failure, and time required. CONCLUSIONS: The interlock and modified Kessler-loop lock techniques for flexor tendon sutures produce similar mechanical characteristics in vitro.